Incidence, recurrence, and case fatality rates for myocardial infarction in southwestern France, 1985 to 1993. Issue 2 (1st August 2000) - Marques-Vidal, P; Ruidavets, J-B; Cambou, J-P; Ferrières, J
Abstract : OBJECTIVE: To assess the impact of incidence, recurrence, and case fatality rates for myocardial infarction on coronary heart disease mortality in southwestern France between 1985 and 1993. DESIGN: Toulouse-MONICA myocardial infarction register. SETTINGS AND PATIENTS: All subjects aged 35 to 64 years living in the French department of Haute-Garonne. INTERVENTIONS: All coronary artery disease events between 1985 and 1993. MAIN OUTCOME MEASURES: 7210 events collected by the register between 1985 and 1993. RESULTS: In men, adjusted attack, total, and out of hospital mortality decreased by 2% (95% confidence interval (CI), −3.8% to −0.1%), 6.2% (95% CI −8.4% to −4.0%), and 4.2% (95% CI −7.0% to −1.5%) a year, respectively (p < 0.05). Incidence and recurrence rates decreased by 2% (95% CI −4.1% to −0.1%, p < 0.05) and 1.9% (95% CI −5.9% to 2.2%) a year (NS). In women, attack, total, and out of hospital mortality decreased by 1.7% (95% CI −5.2% to 1.8%), 4.8% (95% CI −9.6% to 0.1%), and 2.6% (95% CI −9.4% to 4.1%) a year, respectively; incidence decreased by 2% (95% CI −6.5% to 2.5%) and recurrence increased by 1.4% (95% CI −9.8% to 12.6%) a year (all NS). In men, total, incident, and recurrent 28 day case fatality decreased by 3.8% (95% CI −4.8% to −2.8%), 3.2% (95% CI −4.1% to −2.3%), and 6.4% (95% CI −9.5% to −3.3%) a year, respectively (p < 0.05). For women, the corresponding decreases were 3.3% (95% CI −6.1% to −0.6%), 3.3% (95% CI −13.2% to 6.6%), and 11.7% (95% CI −24.6% to 1.3%) a year, but only the decrease in total 28 day case fatality reached significance. In both sexes, the reduction in case fatality contributed nearly 70% of the decrease in myocardial infarction mortality. CONCLUSIONS: In southwestern France, the decrease in myocardial infarction mortality mainly reflects improvements in acute management rather than prevention.